PERKEMBANGAN SISTER CITY SURABAYA-GUANGZHOU DAN DAMPAKNYA TERHADAP KEMAJUAN KOTA SURABAYA - Luluk Erika; Rizki Rahmadini Nurika (Universitas Airlangga, 2020)
Sister city is a concept which refer to a cooperative initiative set upbetween two cities from two different country of origin. Surabaya is one ofwell-known cities in Indonesia which actively engage in such programs,among them are cooperation with Guangzhou, China; Busan, SouthKorea; and Kitayushu, Japan. However, a focus on sister city initiativesbetween Surabaya and Guangzhou seems to be relatively understudied.This research is aimed to uncover the dynamics of Surabaya-Guangzhousister city initiative and how is it impacting Surabaya specifically. Toexplain this, the author put some emphasis on the concept “sister city”and employing Arild Underdal’s Regime Effectivity Model. a qualitative descriptiveresearch method is undergone with data gatehered throughliterature studies, as well as direct interview. This research found thatthe initiative has resulted in relatively ineffective outvomes under theindicator of level of collaboration, problem malignancy, and problemsolving. Nevertheless, the sister city between the two cities has given anumber of contributions to the growth of Surabaya.